The Possibilities and Pitfalls of Talking about Conception with Donor Egg: Why Parents Struggle and How Clinicians Can Help. (2nd January 2016) - Freeman-Carroll, Nancy
ABSTRACT: It can be challenging for parents to talk with their children about gamete donation. Many mothers who chose donor egg, following failed fertility treatments and/or advanced maternal age, do not talk about it with their children. Research has found significant parental anxiety, increasing with time after conception, in parents who have not told their children about their donor origins. A set of common reasons given for a reluctance to talk will be considered, along with its impact on the psychic functioning of parents and children. Talking about donor conception is not a one-time conversation but a process that will evolve over the child's lifetime. Psychological adjustment to the choice of egg donation that can foster disclosure will be discussed, including how couples (1) accept that a donor is required; (2) imagine the donor, who is often anonymous; and (3) incorporate the choice of donor conception into daily family life. There is growing research and psychoanalytic literature on the development of children conceived with gamete donation; however, fewer families of heterosexual parents are included in these follow-up studies because of the prevalence of nondisclosure. This article considers why talking about conception with donor egg is so hard for many families and offers lines of inquiry that may be helpful to these families and the clinicians that will support them.